Evaluation of the safety and immunological effects of Bacillus Calmette–Guérin in combination with checkpoint inhibitor therapy in a patient with neuroendocrine carcinoma: a case report - Konstantin Föhse; Priya A. Debisarun; Gizem Kilic; Joyce M. van Dodewaard-de Jong; Mihai G. Netea (Journal of Medical Case Reports, 2023)
Abstract Background Immune checkpoint inhibitors have revolutionized therapy of advanced and metastatic cancers. However, a significant proportion of patients do not respond to immune checkpoint inhibitors or develop resistance. Therefore, novel therapies or combinations of therapies that may act synergistically are needed. It has been suggested that induction of trained immunity may increase the response to immune checkpoint inhibitor therapy, through reprogramming myeloid cells toward an antitumor phenotype. On the other hand, activation of the immune system also carries the risk of potentially sustaining tumorgenicity and increasing immune- related toxicity. Case presentation We report the case of a 37-year-old Dutch male suffering from gastric neuroendocrine carcinoma with liver metastases and high risk for an unfavorable outcome, who was treated with a combination of programmed cell death protein 1 inhibitor nivolumab and the trained immunity-inducer Bacillus Calmette–Guérin vaccine as a salvage therapy. Three doses of BCG vaccine were administered at 3-month intervals, in conjunction with the immune checkpoint inhibitor regimen. At a certain point, radiation therapy was added to the treatment regimen. During the combination of these therapies, the patient developed immune-mediated colitis, which necessitated discontinuation of all treatments. Bacillus Calmette–Guérin vaccination induced a trained immune response with elevated monocyte-derived interleukin-6 and interleukin-1β production capacity. From the first vaccination with Bacillus Calmette–Guérin until 3 months after the last vaccination with Bacillus Calmette–Guérin, the patient displayed only mild progression of the primary tumor and no progression of the metastases. Conclusion In this study, we show the feasibility to combine checkpoint inhibitor therapy with inducers of trained immunity in a patient with an aggressive neuroendocrine tumor. Autoimmune side effects are common under programmed cell death protein 1 inhibitor therapy, which was considered the most likely cause of colitis, although an additive effect of Bacillus Calmette–Guérin vaccination or radiotherapy cannot be excluded. The patient displayed only mild progression during the combination therapy, but larger studies are warranted to fully explore the potential benefit of trained immunity inducers as an adjuvant to immune checkpoint inhibitor therapy.